Effect of Health Promotion on Immunization on Increasing Maternal Participation and Basic Immunization Coverage in The Village Tanjung Laong Working Area of Technical Implementation Unit of Muara Pahu Public Health Center - Prasetyana, Ely; Sutrisno, Sutrisno; Andraini, Rus (Rifa'Institute, 2023)
Introduction: Complete basic immunization is immunization given to children before the age of 1 year which consists of HB 0 immunization, BCG immunization, DPT-HB-HIB immunization, polio immunization, IPV immunization and measles immunization. The benefit of immunization is to provide immunity to infants in order to prevent illness and death of infants and children caused by frequently infectious diseases. Objective: This study aims to determine the effect of health promotion on immunization on increasing maternal participation and basic immunization coverage in tanjung Laong village, the working area of the Technical Implementation Unit of Muara Pahu Public Health Center Methods: The research design in this study was a quasi-experimental research design with one group pretest-posttest design. The study was carried out in March 2022. The population in this study were allmothers who had infants and toddlers aged 1-12 mounth in Tanjung Laong Village totaling 19 peolple. Results and Discussion: The effect of health promotion on immunization on increasing maternal participation was obtained pValue = 0.003 smaller than 0.05 and the effect of health promotion on immunization on basic immunization coverage obtained pValue = 0.001 smaller than 0.05. Conclusion: There is an effect of health promotion on immunization on increasing maternal participation and basic immunization coverage in Tanjung laong Village, the working area of Technical Implementation Unit of Muara Pahu Public Health Center